Acute retinal necrosis (ARN) in the context of neonatal HSV-2 exposure and subconjunctival dexamethasone: case report and literature review - McGrath, Lindsay; Woods, Marion; Lee, Lawrence; Conrad, Diana (Digital Journal of Ophthalmology, 2013)
HSV-2 is an important cause of the acute retinal necrosis (ARN) syndrome in younger patients. We describe an atypical case of HSV-2 ARN in the context of neonatal exposure and subconjunctival steroid injection. Clinicians should be aware of the association of neonatal or congenital exposure to HSV-2 as a risk factor for this disease because early treatment may improve outcome and/or avoid involvement of both eyes.